2001
DOI: 10.1093/jn/131.3.1006s
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis by Which Garlic Suppresses Atherosclerosis

Abstract: The aim of this study was to determine the mechanism by which the aged garlic extract "Kyolic" has a protective effect against atherosclerosis. Plasma cholesterol of rabbits fed a 1% cholesterol-enriched diet for 6 wk was not reduced by supplementation with 800 microL Kyolic/(kg body. d). In spite of this, Kyolic reduced by 64% (P < 0.05) the surface area of the thoracic aorta covered by fatty streaks and significantly reduced aortic arch cholesterol. Kyolic also significantly inhibited by approximately 50% th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 12 publications
2
55
0
2
Order By: Relevance
“…These insights may help explain positive cardiovascular outcomes of several smaller, randomized controlled trials that utilized garlic or garlic extracts. Results were largely independent of any effects on standard risk factors (222,223,247,939).…”
Section: E Hydrogen Sulfide Signalingmentioning
confidence: 86%
“…These insights may help explain positive cardiovascular outcomes of several smaller, randomized controlled trials that utilized garlic or garlic extracts. Results were largely independent of any effects on standard risk factors (222,223,247,939).…”
Section: E Hydrogen Sulfide Signalingmentioning
confidence: 86%
“…It is interesting that a recent small pilot study by Budoff et al (60) showed that, compared with placebo, AGE may inhibit the rate of progression of CAC in the general population. The mechanism is probably related to their ability to inhibit atherosclerosis (61).…”
Section: Other Interventionsmentioning
confidence: 99%
“…The results of numerous clinical investigations have shown that garlic may produce beneficial effects on different cardiovascular risk factors: garlic is known to reduce serum cholesterol levels in humans, inhibit cholesterol biosynthesis, lower arterial blood pressure, suppress low-density lipoprotein oxidation, lower plasma fibrinogen and increase fibrinolytic activity, thus possessing anti-atherosclerotic properties. [1][2][3][4][5][6] Among all risk factors for atherosclerosis, arterial hypertension, along with dyslipidemia, is thought to be the most potent factor that greatly increases the risk of cardiovascular diseases. 7,8 Clinical investigations that focused on the effect of garlic in arterial hypertension have revealed its moderate hypotensive action in most studies; [9][10][11][12][13] however, controversial data exist.…”
Section: Introductionmentioning
confidence: 99%